Pemeranan dan Internalisasi Karakter Integritas dalam Pelayanan Literasi Masyarakat - Kurniawan, Heru; Rahayu, Sri (Komisi Pemberantasan Korupsi, 2020)
Literacy service of Rumah Kreatif Wadas Kelir Community is carried out through communication and interaction between volunteer and society. The service includes borrowing and returning literacy book, educational and religious activity, skill assistance, and financial service. In this literacy service, the volunteers portray integrity character based on moral ethic and humanity. The integrity character plays a vital role in enhancing society trust which in turn significantly contribute to the development of Rumah Kreatif Wadas Kelir Community. The success of this integrity character implementation means that the internalization of integrity character in society has been successfully carried out. In addition, the integrity character has become a collective character that is upheld by society in enhancing their dignity and improving their environment. The Integrity character of society significantly contribute to the development of both society and Rumah Kreatif Wadas Kelir Literacy Community concerning education, economy, religion, and socio-culture.